Vertebral refracture after percutaneous vertebroplasty for osteoporotic vertebral compression fractures with and without brace wearing: A retrospective study of 300 patients - Xinyu, Guo; Na, Zhu; Haihong, Zhang; Dingjun, Hao (Frontiers in Surgery, 2023)
Background The aim of the study was to examine the clinical incidence rate of vertebral body fractures after percutaneous vertebroplasty (PVP) with and without brace wearing and provide a new guiding ideology for preventing vertebral fractures after clinical surgeries. Methods The retrospective analysis included 100 outpatients who underwent PVP between January 2017 and December 2018 without bracing after PVP surgeries (non-brace-wearing group). In total, 100 patients were paired into the rigid brace group and 100 patients were paired into the soft braces group according to propensity score matching. Seven independent variables were used in the soft and rigid brace group: age, sex, body mass index (BMI), visual analog scale (VAS), Oswestry Disability Index (ODI), and Cobb angle. The VAS, ODI, and Japanese Orthopaedic Association (JOA) scores were recorded preoperatively on the second day, after 1 month, after 3 months, and during the last follow-up postoperatively. We recorded the incidence of vertebral refracture in each of the three groups of patients and evaluated the effect of braces on postoperative fractures based on the ODI, VAS, and JOA scores. Results All patients were followed up for 8–24 months (mean 22.4 months). Compared with the preoperative values, the age, sex, BMI, bone density, ODI, VAS, and Cobb angle between refracture and non-refracture were not statistically significant. The VAS, ODI, and JOA scores significantly increased in the brace-wearing group compared with those of the non-brace-wearing group (p < 0.05). The incidence of vertebral refracture in the brace-wearing group was lower than that in the non-brace-wearing group, between which there was a significant difference (p < 0.05). Three months postoperatively, the JOA score of the soft brace group was significantly higher than that of the rigid brace group (p < 0.05). During the last follow-up, it was found that there was no difference in the VAS score, the incidence of refracture, or ODI between the soft brace group and the rigid brace group (p > 0.05). The improvement in the JOA score of the soft brace group was better than that of the rigid brace group, between which there was a significant difference (p < 0.05). Conclusion Braces can improve the prognosis of quality of life and postoperative subjective perception, whose presence can relieve postoperative residual pains. In contrast, patients can have a better medical experience wearing a soft brace.